APPLICATION OF H. MINSKI THEORY FOR DEVELOPING EARLY WARNING INDICATORS OF FINANCIAL INSTABILITY IN THE CREDIT SEGMENT OF THE FINANCIAL SECTOR - Хуторна, Мирослава (Socio-economic relations in the digital society, 2019)
The effectiveness of the fi nancial stability ensuring of the fi nancial sector’s credit segment directly dependsif signs of its financial fragility are identifi ed at the appropriate time. In this paper the author suggests a methodological approach to the indicative estimation of economic preconditions of credit institutions’ financial stability, using the theory of financial instability by H. Minsky. Proposals are developed in three directions. First, it is substantiated the relationship between the types of economic environment formed by economic entities in income-debt relations (we mean hedge, speculative, and Ponzi states) and the potential level of fi nancial stability of the credit segment. Second, the main terms of Minski theory are extrapolated on credit institutions; the features of their activity using hedge, speculative or Ponzi financing for their obligations fulfilmentare determined; it is formulated the hypothesis that the potential level of financial stability of the credit segment is determined by the fi nancing regimes used by credit institutions and economic agents of the non-fi nancial sector to fi nance their investments and obligations in general.Third, indicators for assessing the economic preconditions for financial stability of the credit sector of the financial sector have been developed.Th e further research will be devoted to verifi cation of the higher mentioned hypothesis. Another perspective task is to form indicators for identifying hedge, speculative, and Ponzifi nancing credit institutions.
Keywords: credit segment of financial sector; financial stability; potential level of financial stability; indicative assessment method; principles of economic indicators formation; hedge economic environment; speculative economic environment; Ponzi-state